POLITICAL CAMPAIGN LANGUAGE ON THE OUTDOOR MEDIA: IS IT A REGISTER? - Nana Raihana Askurny (Kantor Bahasa Kepulauan Riau, 2018)
The election of district chiefs (Pemilihan Kepala Daerah: Pilkada)took place in all Indonesia provinces, in 2018. Tanjungpinang, the capital city of Riau Islands province also performs this such election. There are two couples of candidates who compete in achieving people votes. The candidates organized their ideas, visions, missions, by using the outdoor medias, like banners, billboards, posters, and street furniture. This study attemps to find out the surface construction of the election of district chiefs sentences of political campaign. This is a linguisticresearch. It analysed the language use in political aims in terms of register. Register is a language variety which applies a set of specific vocabularies and speech acts. And it also defines mode, setting, and topic of utterances. The researcher uses descriptive qualitative approach, in which data are collected, categorized, and analysed. The data collection conssists of words, phrases, and clauses on the outdoor media. Specific vocabularies of each candidate occured distinctively. Like the word,” sabar”, “baik”, “agen perubahan”, “Tanjungpinang baru”, are frequently occured by candidate number one. While, the words, “lanjutkan pembangunan”, “laman hati”,” rajut”, and “doa” are applied by candidate number two. The use of commissive acts are effective to deliver aims and intention of candidate, which is proved the candidate who used mostly commissive acts won the election.This research comes to the result that political campaign in Tanjungpinang remains as a register. AbstrakPemilihan kepala daerah (Pilkada) terjadi di seluruh provinsi Indonesia, pada tahun 2018. Tanjungpinang, ibu kota Provinsi Kepulauan Riau juga melakukan pilkada ini. Ada dua pasangan calon yang bersaing dalam meraih suara masyarakat. Para kandidat mengorganisasikan ide, visi, misi, dengan menggunakan media luar ruang, seperti spanduk, baliho, poster, dan perabot jalan. Penelitian ini mencoba mengetahui konstruksi permukaan kalimat pilkada kampanye politik. Penelitian ini adalah penelitian linguistik. Penelitian ini menganalisis penggunaan bahasa dalam tujuan politik dalam hal register. Register adalah variasi bahasa yang menerapkan seperangkat kosakata dan tuturan tertentu. Register juga menjelaskan tentang mode, pengaturan, dan topik ujaran. Peneliti menggunakan pendekatan kualitatif deskriptif, yaitu dengan cara, data dikumpulkan, dikategorikan, dan dianalisis. Pengumpulan data terdiri atas kata-kata, frasa, dan klausa pada media luar ruang. Kosakata spesifik dari masing-masing kandidat muncul secara khusus. Seperti kata, “sabar”, “baik”, “peniti”, “Tanjungpinang baru”, sering terjadi oleh kandidat nomor satu. Sementara, kata-kata, “lanjutkan pembangunan”, “laman hati”, “rajut”, dan “doa” digunakan oleh kandidat nomor dua. Penggunaan tindakan komisif efektif untuk menyampaikan tujuan dan niat kandidat, yang terbukti kandidat yang paling banyak menggunakan tindakan komisif memenangkan pilkada. Hasil dari penelitian ini menunjukkan bahwa kampanye politik di Tanjungpinang tetap sebagai register.Kata kunci: media luar ruang, kampanye politik, dan tindak tutur